Employment as the Most Important Factor in Poverty Reduction - M. M., Mukhammedov; S. A., Iskhakova (International Journal on Integrated Education, 2023)
This article examines the relationship between employment and poverty reduction in Uzbekistan. The introduction highlights the importance of poverty reduction as a social policy objective and the negative effects of poverty on individuals and society. The main part of the article discusses the definition of employment and its significance as a socio-economic indicator, as well as the problems faced by the labor market in Uzbekistan. In conclusion, the article emphasizes the need for strategic solutions to employment issues in order to improve the standard of living and competitiveness of the country.